Impact of Next-Generation Computed Tomography Scanners on Image Quality and Radiation Dose in Cardiac CT Outpatient Imaging - Michaely, Henrik Jakob; Lueck, Melanie; van Rickeln, Miriam (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Retrospective analysis of 245 consecutive cardiac CTA cases before and after transition from a 128-slice single-source CT scanner (SSCT, Definition AS+, temporal resolution 150ms, detector width 38.4mm) to a 128-slice dual-source CT scanner (DSCT, Pro.Pulse, 86ms, 38.4mm).A total of 113 patients (33f/80m, mean age 66.0 years) were examined using the SSCT scanner, while 132 patients (43f/89m, 64.7 years) were examined using the DSCT scanner. Protocol selection (sequential/spiral) was performed manually on the SSCT scanner. On the DSCT scanner, protocol selection was automated using built-in AI. Heart rate, kV for CTA, and DLP (mGy·cm) for CTA were recorded. Image quality was independently evaluated for the RCA, LM, LAD, and LCX by two experienced readers on a three-point ordinal scale: 3 – excellent, 2 – minor artifacts but diagnostic, 1 – artifacts rendering vessel evaluation incomplete.The mean heart rate of the patients was not significantly different between the SSCT scanner (61.1 bpm) and DSCT scanner (61.6 bpm). The mean kV for CTA was 101.4 on the SSCT scanner and 74.2 on the DSCT scanner (p<0.0001). The mean radiation dose for cardiac CTA, measured as DLP, was 134.2 on the SSCT scanner, 53% higher than the 87.7 on the DSCT scanner (p=0.001). For the SSCT scanner, 32% and 37% of RCAs were non-diagnostic according to readers 1 and 2, compared to 3% and 2% for the DSCT scanner. For the LM, LAD, and LCX, the rate of non-diagnostic cases was 2–7% with the SSCT scanner and 0–1% with the DSCT scanner.Under otherwise unchanged external conditions, the switch from SSCT to DSCT scanner for cardiac CT resulted in a significant reduction in radiation dose by approximately 34%, along with a significant decrease in non-diagnostic examinations.
Keywords: heart; CT-angiography; cardiac ct; dual-source ct; image quality; radiation dose